Efek Pemberian Pupuk Organik Cair (POC) NASA Terhadap Pertumbuhan dan Hasil Dua Varietas Tanaman Padi Ketan (Oryza sativa glutinosa L.) - marisa nurindah sari (AGRONISMA, 2021)
The latest technology that is very dominant in increasing plant productivity is the use of superior varieties. In addition, fertilization is also a determining factor for plant productivity. NASA liquid organic fertilizer (POC) is applied through the leaves and is able to increase the growth and yield of glutinous rice plants. This study aims to determine the response to growth and yield of glutinous rice plants due to the addition of liquid organic fertilizer (POC) NASA at different dose levels with two kinds of glutinous rice varieties and their combinations. This research was conducted from October 2020 to March 2021 in Dermo Hamlet, Mulyoagung Village, Dau District, Malang City. Using a Divided Plot Design (RPT) compiled with a 2-factor Randomized Block Design (RAK). The first factor is the dose of Nasa Liquid Organic Fertilizer (POC) (D), which consists of 3 levels, namely: d1 = 1 ml L-1, d2 = 3 ml L-1 and d3 = 5 ml L-1. While the second factor is the type of glutinous rice plant variety (V) which consists of 2 types, namely: v1 = Grendel variety and v2 = Lusi variety. Statistical test of ANOVA analysis of variance and 5% BNJ follow-up test. The results of analysis of variance (ANOVA) showed that in general, the combination of NASA POC dose treatment with glutinous rice varieties did not interact with plant growth and yield parameters. However, at the parameters of leaf area at 21 DAP, stem diameter at 49 DAP and the number of panicles per clump there were interactions. Separately, the NASA POC dose treatment had a significant effect only on the milk maturity parameter. Furthermore, the treatment of glutinous rice varieties gave a significant effect on the parameters of plant growth and yield. The best response was generally shown by the Lusi variety of glutinous rice.